Порівняльний аналіз щодо використання об’єктів інтелектуальної власності в країнах світу та в Україні - Черепанова, Вікторія Олександрівна; Силка, Ігор Васильович (Кременчуцький національний університет ім. Михайла Остроградського, 2020)
Розроблено заходи щодо покращення управління об’єктами інтелектуальної власності промислових підприємств на базі аналізу публікацій за останні роки та статистичної інформації зібраною організаціями ВОІВ (Всесвітня Організація Інтелектуальної Власності), і Українським інститутом інтелектуальної власності – Укрпатент (Україна). За допомогою даних цих організацій проведено об’єктивний аналіз статистичної інформації та визначено положення та тенденції розвитку України й підприємств щодо сучасного стану інтелектуальної власності. Зроблено висновок, що за останні роки збільшився інтерес науковців різних країн світу до проблем функціонування об’єктів інтелектуальної власності. Встановлено, що найбільший інтерес вчених світу стосується законодавства країн щодо методів захисту та підтримки інтелектуальної власності. Аналіз країн світу та України за напрямами заявок на винаходи, промислові зразки, та інші об’єкти показав, що в розвинутих країнах світу спостерігається тенденція зростання кількості заявок, особливо у промисловості, в Україні – падіння інтересу до винахідницької діяльності. В Україні спостерігається динаміка спаду подачі заявок близько 5% щороку, крім заявок на знаки для товарів та послуг, де за останні чотири роки зростання досягло 29%. Тому, в сучасних реаліях України існує гостра потреба щодо вдосконалення системи управління інтелектуальною власністю на всіх рівнях (макро-, мезо- та мікро-) управління, особливо у галузі законодавства та стимулювання розвитку інтелектуальної власності на рівні окремого підприємства.

Purpose. Every year, the technological development becomes even more intensive, resulting in an increase in the value of information that is expedient to be used to increase productivity and product quality. The society transition to the use of the innovative technologies and equipment obliges companies worldwide to search for new developments, their implementation in the production process and protect their intellectual property. Increasing inventions portfolio promotes companies competitiveness, being more attractive to investors and attracts more investments. Methodology. The purpose of this work is to develop measures to improve the industrial enterprises intellectual property management based on the analysis of publications in recent years and statistical information collected by WIPO (World Intellectual Property Organization) and the Ukrainian Institute of Intellectual Property - Ukrpatent (Ukraine). Results. Based on these organizations data, an objective analysis of statistical information was conducted, and guidelines and trends of Ukraine and enterprises development were determined with respect to the current status of intellectual property. It is concluded that the interest of scientists from different countries of the world has increased in recent years to the problems of intellectual property assets functioning. This is especially true for lines of innovative methods application for search and protection of the rights of specific entities that are associated with neural networks and computer data processing. It has been found that the greatest interest of scientists worldwide lies with legislation of countries regarding the methods of intellectual property protection and support. Originality. Analysis of the countries throughout the world and Ukraine, in particular, in the areas of applications for inventions, industrial prototypes and other assets, witnessed the growth trend in applications number in developed countries, especially in industry sector, while in Ukraine – the decline of interest in inventive activity. Negative dynamics in applications filing is observed in Ukraine, which makes about 5% annually, except the applications as to the marks for goods and services where the growth has reached 29% within the last four years. Practical value. Therefore, in Ukraine's contemporary realities there is an urgent need to improve the system of intellectual property management at all levels (macro, meso and micro) management, especially in legislation and encouraging the development of intellectual property at the level of a specific enterprise.
Comparative analysis of intellectual property assets use worldwide and in Ukraine
Keywords: промислові підприємства; винаходи; корисні моделі; винахідницька діяльність; управлінські рішення; industrial enterprises; inventions; useful models; industrial prototypes; intellectual property